Perbandingan model problem based learning (PBL) dan model pembelajaran konvensional terhadap hasil belajar IPS terpadu siswa SMP Negeri 6 Welak - Maria Melita R. Jemalu; Rusno Rusno; Udik Yudiono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This study focuses on discussing the results of the analysis of (1) the value of integrated social studies learning outcomes of students who are taught using the Problem based learning (PBL) model, (2) the value of integrated social studies learning outcomes of students who are taught using conventional learning models, (3) comparison of the results of Integrated Social Studies learning students who are taught using the Problem based learning (PBL) model with the value of Integrated Social Studies learning outcomes students who are taught using conventional learning models. This research method is quantitative with a quasi-experimental design. The population of this study was students of class VIII A and VIII B of SMP Negeri 6 Welak 2020/2021, with a total of 50 students (classes VIII A and VIII B each consisted of 25 students). Sampling uses total sampling, so that all members of the population are assigned to be the sample, where class VIII A is assigned to be the experimental class and class VIII B is assigned to be the control class. The treatment of the PBL model was only applied to the experimental class, while the control class was taught by the teacher using a conventional learning model. This research data collection using test technique. Data analysis techniques include normality test, homogeneity test, and Independent Sample T Test. The results of this study conclude: (1) the value of Integrated Social Studies learning outcomes for class VIII students of SMP Negeri 6 Welak who are taught using the Problem based learning (PBL) model is in the 'very good' category; (2) the value of Integrated Social Studies learning outcomes for grade VIII SMP Negeri 6 Welak students who are taught using conventional learning models are in the 'good' category; (3) the value of Integrated Social Studies learning outcomes for students of class VIII SMP Negeri 6 Welak who are taught using the Problem based learning (PBL) model is significantly different from the value of Integrated Social Studies learning outcomes of students who are taught using conventional learning models.